Effects of combining sensory-motor exercises with transcranial direct current stimulation on cortical processing and clinical symptoms in patients with lumbosacral radiculopathy: An exploratory randomized controlled trial. - Soheila Qanbari; Roya Khanmohammadi; Gholamreza Olyaei; Zohreh Hosseini; Hanie Sadat Hejazi (PLoS ONE)
Background Chronic low back pain (CLBP) is linked to reduced excitability in the primary motor (M1) and sensory (S1) cortices. Combining sensory-motor exercises with transcranial direct current stimulation (tDCS) to boost M1 and S1 excitability may improve treatment outcomes. This combined approach aligns with the neurophysiological mechanisms underlying CLBP and may target the neuroplastic changes induced by low back pain. This study aimed to assess whether enhancing M1 and S1 excitability via tDCS, alongside sensory-motor exercises, offers additional benefits for CLBP patients. Method Participants were randomly assigned to receive either real or sham tDCS alongside sensory-motor exercises. Outcome measures included pain intensity, disability level, motor control ability, amplitudes of N80 and N150, and the amplitude of motor-evoked potential (MEP) and active motor threshold (AMT) for the multifidus (MF) and transversus abdominis/internal oblique (TrA/IO) muscles. A linear mixed-effects model (LMM) analyzed group, time, and interaction effects, while Spearman's correlation assessed relationships between neurophysiological and clinical outcomes. Results The results showed significant reductions in pain intensity and disability levels (P < 0.001) and improved motor control (P < 0.001) in both groups. Both groups also exhibited increase in MF MEP amplitude (P = 0.042) and N150 amplitude (P = 0.028). The tDCS group demonstrated a significant decrease in AMT of MF and TrA/IO muscles (P < 0.05) and an increase in N80 amplitude (P = 0.027), with no significant changes in the control group. Additionally, the tDCS group had significantly lower AMT for the TrA/IO muscle in the post-test compared to the sham group (P = 0.001). Increased N150 amplitude was correlated with improved motor control. Conclusions The findings showed that sensory-motor exercises combined with either tDCS or sham tDCS effectively reduced pain intensity, decreased disability, and improved lumbar motor control in lumbosacral radiculopathy patients. No significant differences were observed between groups, indicating no added clinical benefit from tDCS over exercises alone. However, both groups demonstrated increased N150 and MF MEP amplitudes, suggesting enhanced cortical excitability in motor and sensory regions. While clinical outcomes were similar, neurophysiological data indicate that sensory-motor exercises play a central role in boosting cortical excitability, with tDCS further amplifying this effect, as evidenced by a significant AMT reduction in MF and TrA/IO muscles and an increase in N80 amplitude.